REPERCUSSÕES EMOCIONAIS EM PROFISSIONAIS DA PSICOLOGIA NO CONTEXTO DA PANDEMIA DE COVID-19 - BORGES, Gabriela Cardoso (2024)
Research indicates that the pandemic caused by the new coronavirus (COVID-19) caused a serious epidemiological crisis, with consequences for physical health and damage to emotional health. Throughout the pandemic, care professionals presented emotional manifestations, such as symptoms of depressed mood, anxiety, burnout, emotional exhaustion and work overload. In the face of emotional health problems, psychology played an active role in assisting hospitalized patients and their families. During the pandemic, the Psychologist dealt with demands regarding the collective fear expressed by the population. Given this context, the present study aimed to understand the emotional repercussions of psychology professionals working in the context of the COVID-19 pandemic. For this, a study was carried out with a descriptive design and qualitative approach. The investigation took place through semistructured interviews and convenience sampling. To collect the data, a sociodemographic questionnaire and a semi-structured interview script (via Google form) were used. To analyze the data, content analysis was used according to Minayo. 30 professionals were interviewed, two of which were eligible for analysis and discussion. The results allow us to discuss the difficulties faced by these professionals regarding: the professional helplessness of professionals in direct assistance to Covid-19, the personal experiences of the psychologist during the pandemic regarding their fears regarding contamination, death, health problems physical and emotional, changes in life routine, the attitude towards online service understood as a possibility of expanding services and the difficulties in adapting to the electronic environment, representations regarding vaccination, the ambivalent attitude towards the end of the pandemic and the help of psychotherapy as self-care. Psychology professionals experienced moments of fragility, in many circumstances their personal demands were in line with those of their patients. In this way, the discussion of health professional prolapse contributes to problematization about the health of those who are committed to caring for others.